2022
DOI: 10.1007/s10067-022-06185-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensory testing and topical capsaicin can characterize patients with rheumatoid arthritis

Abstract: Background and objectives Our study aimed at examining the long-time inflammatory effects of rheumatoid arthritis (RA) as chronic immune-mediated disease on pain sensation and neuropathy development compared to healthy subjects (HS). Methods We used the quantitative sensory testing (QST) protocol of the German Research Network on Neuropathic Pain and Electroencephalography (EEG)–based contact heat evoked potentials (CHEPs) before and after topical capsaici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In order to avoid peripheral sensitization or stimulus wind up due to repetitive stimulation, both mechanical and contact heat stimulation were applied 12 times with a randomized or pseudo-randomized inter-stimulus interval. The number of trials in the literature ranges from 7 trials (Granovsky et al 2016;Anders et al 2022) up to 20 trials (Rosner et al 2018). We stimulated an area of 9 cm × 8 cm on the dorsal area of the dominant foot and applied the stimuli in a randomized pattern across the whole stimulation area.…”
Section: Standardized Noxious Stimulationmentioning
confidence: 99%
“…In order to avoid peripheral sensitization or stimulus wind up due to repetitive stimulation, both mechanical and contact heat stimulation were applied 12 times with a randomized or pseudo-randomized inter-stimulus interval. The number of trials in the literature ranges from 7 trials (Granovsky et al 2016;Anders et al 2022) up to 20 trials (Rosner et al 2018). We stimulated an area of 9 cm × 8 cm on the dorsal area of the dominant foot and applied the stimuli in a randomized pattern across the whole stimulation area.…”
Section: Standardized Noxious Stimulationmentioning
confidence: 99%
“…A noxious thermal stimulus task was chosen because prior work has shown that sensitivity to and descending modulation of noxious thermal stimuli discriminates patients rheumatoid arthritis from controls [1; 15; 64].…”
Section: Methodsmentioning
confidence: 99%
“…The brain activity information extracted from electroencephalography (EEG) can be used as a biomarker of pain signals, that is, relatively independent of subjective influence. For instance, EEG-based contact heat-evoked potentials can provide objective responses during QST that are not dependent on the subjective characteristics of the tester or examinee ( Granovsky et al, 2016 ; Anders et al, 2022 ). Thus, the first goal of this study was to combine the QST, in the form of electrical stimuli provided by a commercial PainVision system, with simultaneous EEG recording.…”
Section: Introductionmentioning
confidence: 99%